Pengobatan Infertilitas Dalam Hukum Islam - Adrianto (Institut Syekh Abdul Halim Hasan Binjai, 2024)
Having children is one of the goals of marriage, namely preserving the offspring to be achieved. But as time goes by, husband and wife have not got obtain offspring, due to several things; Among the reasons is infertility in husband and wife. husband and wife who does the treatment infertility, and live a healthy lifestyle,and do the program pregnancy by natural with sex, then it can produce the desired pregnancy. This is influenced by internal factors and external. This article aims to explore or find the law of medicine infertility (fertility disorders on husband and wife have), by using ushuli approach, as namely analyzing the main points of the problem By using maslahah theory dan maqashid al-syari'ah. This research is research bibliography by method descriptive analysis, namely Analyzing treatment habbatussaudah with scholars classic, analyzing technology treatment infertility by using theory maslahah dan maqashid al-syari'ah. Results of this research, treatment technology of infertility in Islamic Law is can And in accordance with the principles Islamic treatment. Malik use maslahah with istinbath, and ghazali use maslahah with objective of kind and not violate with objective of syariah.